TAM to Measure Electric Motorcycle Adoption Interest in West Kalimantan - Asri Hidayati; Adiyath Randy Yudimamase; Henrian Stiawan (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research examines the factors that affect the interest in adopting electric motorcycles in West Kalimantan, using an extended version of the Technology Acceptance Model (TAM). It explores how perceived usefulness (PU), perceived ease of use (PEOU), and crucial external variables like perceived enjoyment (PE), compatibility (C), and perceived resources (PR) affect adoption intentions. Methodology/approach: This study adopted a quantitative methodology, gathering data from an online questionnaire completed by 200 purposively sampled respondents in West Kalimantan. The collected data were subsequently analyzed using Structural Equation Modeling (SEM) with the AMOS software, employing Maximum Likelihood (ML) estimation to test the relationships. Results/findings: The study finds that PEOU positively and significantly influences both PU and BI. PU also significantly affects adoption intentions. Crucially, external factors like PE and C were found to significantly shape these core perceptions, While PR did not show a statistically significant impact on either PEOU or PU. Conclutions: Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) are the primary factors driving the intention to adopt electric motorcycles in West Kalimantan., with PEOU emerging as the most dominant factor. The extended TAM model validates that external variables like enjoyment and compatibility influence these initial perceptions, while perceived resources play a negligible role at this early stage of interest formation. Limitations: The study's non-probability sampling method and cross-sectional data collection limit generalizability. Contribution: This research provides valuable insights into technology adoption within green transportation, offering practical recommendations for manufacturers and policymakers to accelerate the transition.